Optimization Design and Grasping Stability Analysis of Under-actuated Multi-finger Manipulator - Xiangpeng Lei; Shufeng Tang; Wei Liang; Zirui Guo (Jixie chuandong)
Aiming at the multi-mode grasping problem of the under-actuated manipulator， an under-actuated manipulator with detachable fingers and composite grasping function is proposed. In order to study the grasping performance of the under-actuated manipulator， a spring-adaptive three-knuckle finger mechanism and a double four-link three-knuckle finger mechanism are developed respectively. Both finger mechanisms use the motion principle of four-link mechanism. The nature of the finger greatly affects the grasp stability of the under-actuated manipulator. The properties of a single finger of an under-actuated manipulator are analyzed， and the influence of the position of the joint contact point and the contact force on the grasp stability is analyzed. A theoretical analysis method of the contact force and moment balance is proposed， and the factors affecting the grasping stability factor are discussed.